Renewable energy resources: Combustion and environmental impact of diesel with pyrolytic and biodiesel blends. Issue 4 (June 2023) - Sönmez, Halil İbrahim and Okumuş, Fatih and Safa, Aykut and Aydin, Zafer and Kaya, Cenk and Kökkülünk, Görkem
The worldwide increasing energy demand, interest in alternative energy production and limited resources have made it inevitable to turn to recovering wastes, such as waste tires. Waste tires with annual increase of 2%, corresponding to significant reserves all over the world, brings a serious environmental pollution. In this study, energy recovery was planned considering environmental pollution caused by waste tires and waste cooking oils, both. Accordingly, performance and emission analyzes were carried out using fuels formed by mixing pyrolytic oil obtained from waste tires (WTPO) and biodiesel obtained from waste cooking oil with diesel fuel in a single cylinder engine. The experiments are carried out at 2800 rpm and at full load condition. The findings of engine performance and exhaust emissions were evaluated. While the maximum brake specific fuel consumption (Bsfc) value was determined as 2100 g/kWh for blend fuel of 30% biodiesel and 10% WTPO in diesel fuel, the maximum brake thermal efficiency (Bte) value was determined as 33.541% for P30 fuel. The crank angles yielding maximum in-cylinder pressures approach to top dead center, with increasing biodiesel fraction while keeping WTPO fraction constant. While the increase in the amount of WTPO in the test fuels has an effect on the increase of CO emissions, and increasing biodiesel ratio has reduced the CO emissions. Also the use of biodiesel without WTPO increases NOx emissions slightly, while providing an effective reduction at high WTPO fractions. At low WTPO fractions, biodiesel has reduced HC emissions, while at high WTPO fractions has increased.